Chapter The virus of fashion. Democratization of luxury and new commercial strategies in early modern Valencia - Muñoz Navarro, Daniel (Datini Studies in Economic History, 2022)
This work intends to analyze how the influence of fashion in eighteenth-century Spain transformed the commercial structure, being the petty bourgeoisie the main protagonists and the shop ("botiga") the priority scenario of these changes. To do this, we will focus on eighteenth-century Valencia as a case study, a dynamic city that experienced a remarkable economic development during this century. Undoubtedly, fashion stimulated economic growth not only in the more developed regions of north-western Europe, but this process was also present in the Mediterranean context, developing an important sector of petty bourgeoisie mercantile and a change in the consumption patterns of most of its population.